Analisis Pengaruh CAR, NPL, dan LDR Terhadap Profitabilitas pada Perusahaan Perbankan - Agustiningrum, Riski (E-Jurnal Manajemen; Vol 2 No 8 (2013), 2013)
This research was conducted at the banking company in Indonesia Stock Exchange 2009-2011. Research to look at the relationship between the Capital Adequacy Ratio (CAR), Non Performing Loan (NPL), and Loan to Deposits Ratio (LDR) to profitability (ROA) with a sample of 26 banking companies. Problem solving using multiple linear regression analysis techniques. Based on the analysis it is known that the CAR  no significant effect on profitability (ROA). NPL significant negative effect on profitability (ROA), otherwise Loan to Deposits Ratio significant positive effect on profitability (ROA). Keywords : CAR , NPL , LDR , profitability .